2019
DOI: 10.1055/s-0039-1683896
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Ventilator Strategies in Acute Respiratory Distress Syndrome

Abstract: Mechanical ventilation practices in patients with acute respiratory distress syndrome (ARDS) have progressed with a growing understanding of the disease pathophysiology. Paramount to the care of affected patients is the delivery of lung-protective mechanical ventilation which prioritizes tidal volume and plateau pressure limitation. Lung protection can probably be further enhanced by scaling target tidal volumes to the specific respiratory mechanics of individual patients. The best procedure for selecting opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 145 publications
(145 reference statements)
0
9
0
1
Order By: Relevance
“…The microthrombi may cause altered lung perfusion and hypoxic vasoconstriction, worsening the hypoxemia [16]. Prone positioning may help by improving ventilation-perfusion ratio by changing vascular flow distribution in the pulmonary vessels, and not by recruitment as in the case of ARDS [17].…”
Section: Introductionmentioning
confidence: 99%
“…The microthrombi may cause altered lung perfusion and hypoxic vasoconstriction, worsening the hypoxemia [16]. Prone positioning may help by improving ventilation-perfusion ratio by changing vascular flow distribution in the pulmonary vessels, and not by recruitment as in the case of ARDS [17].…”
Section: Introductionmentioning
confidence: 99%
“…The disease severity, clinical management, ventilator properties, and clinical interventions warrant further exploration of outcomes with a multivariate modeling approach. Considering the patient’s clinical features, physiological status, and response to ventilatory support to determine how to optimally ventilate the patient is of great importance [ 31 ]. A study showed that the use of a reduced tidal volume and avoidance of high airway pressures were associated with improved mortality when compared with a conventional ventilatory approach [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Microthrombi occurring in the pulmonary vasculature in COVID-19 has been postulated to be responsible for hypoxia as it alters lung perfusion, impairs gas exchange and results in loss of oxygen transfer capacity of haemoglobin. It is further proposed that if these processes are not identi ed and managed early through anti-in ammatory medication, lung recruitment strategies such as awake prone ventilation and anticoagulation (9,12), they may lead to rapid clinical deterioration requiring more expensive interventions such as invasive ventilation and often lead to poor clinical outcomes as was noted in our rst patient.…”
mentioning
confidence: 91%